Formação de nutricionistas: uma discussão a partir da análise e interpretação das significações constituídas pelos discentes nas atividades de estágio curricular - Machado, Virgínia Campos (2014)
This thesis aimed to discuss the formation of nutritionists from the analysis and interpretation of meanings that Nutrition students constituted in the traineeship activities. As a theoretical and methodological framework, we adopt the dialectical and historical materialism (Marx and Engels) and socio-historical psychology (Vygotsky and his followers). This is the theory base that enables the construction of theories that recognize the subjective aspects as constitutive of reality and therefore inseparable from discussions about the health-disease process on Nutrition and on training of nutritionists. The field research was developed with the participation of four (4) students from the Nutrition course of Federal University of the Jequitinhonha and Mucuri (UFVJM) that were enrolled in the disciplines of Integrated Stage (corresponding to Stage I in Nutrition and Social Administration of Food Units and Nutrition I), Internship in Clinical Nutrition I, Nutrition Social II and Administration of Food Units and Nutrition II. We use as instruments of the production of data, the drafting Written Narratives and its discussion in Discussion Narratives Sessions, moment that we consider essential to the qualification of the information obtained. The speeches of students were transcribed and to carry out the analysis and interpretation, we were inspired by Aguiar and Ozella (2006, 2013) Meaning Nuclei proposal. We developed four (4) Meaning Nuclei, which are: 1) The dialectic of recognition in the trainee-patient relationship, 2) The (not) intern's place, 3) The meanings of the relationship between theory and practice and 4) Mediations of the process of teaching and learning: some elements highlighted. This thesis realizes one of the possibilities of joint of the contributions of Social Sciences and Humanities to the field of health and proposes the challenge to understand the formation process of nutritionists in its becoming. The syntheses developed in this study allow to think the humanist nutritionist, critical and generalist, as a subject who shares knowledge and specific expertise competence of the nutritionist's profession and that, in the exercise of their profession activity, they do not lose sight of what is the main goal, to whom it's meant to or the concrete conditions that determine it. This reflection seems fundamental so we can move towards that the nutritionist activity is performed as praxis